A continuous preparation method for high conductivity carbon nanotube fibers
By uniformly dispersing the use of sodium taurine gall acid in the preparation of carbon nanotubes, combined with the process of squeezing, solidification, and twisting treatment, the problem of using toxic chloro -sulfonic acid in existing technologies has been solved. Continuous preparation and industrialization of carbon nanotimal fiber.
Patent Information
- Application Number
- CN202410073044.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-18
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-01-18
AI Technical Summary
In the existing carbon nanotube fiber preparation technology, chlorosulphonic acid that is unfriendly and toxic to the human body is required, which limits its industrial production and application.
By dispersing carbon nanotubes with sodium taurite sodium taurite, a carbon nanotuba dispersed liquid, and gel fiber was squeezed into a solidified bath into a solidified bath, and then twisted treatment and rolling wrapping collection to achieve a high conductivity rate Continuous preparation of carbon nanotimal fibers.
The continuous preparation of high -conducting carbon nanotherapy fibers is achieved, and the use of toxic chemical solvents is avoided, the fiber's conductivity and strength are improved, and it is suitable for industrialized production and application.
Smart Images

Figure CN117904751B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-performance carbon nanotube fiber preparation, and in particular to a continuous preparation method of high-conductivity carbon nanotube fibers. Background Art
[0002] Carbon nanotube fibers have excellent electrical, mechanical and thermal conductivity, and are high-quality candidate materials for national projects such as military, national defense, and aerospace. At the same time, with the rapid development of the intelligent era, medical monitoring, human protection, flexible electronic products and other fields also urgently need high-performance fiber materials as support. However, the continuous preparation and industrial production of high-performance carbon nanotube fibers are still key issues that need to be solved. How to develop or improve the preparation method of carbon nanotube fibers is an important scientific research issue related to people's livelihood and development.
[0003] At present, after more than 20 years of development, researchers have developed three main carbon nanotube fiber preparation technologies, namely solution spinning, array spinning and floating catalyst chemical vapor deposition direct spinning. Among them, the carbon nanotube fibers prepared by solution spinning have an absolute advantage in conductivity, and this technology draws on a large number of relatively mature industrial technologies and has good prospects for large-scale application.
[0004] At present, the main research direction of solution spinning technology is liquid crystal spinning technology, that is, through the spontaneous dissolution of carbon nanotubes by chlorosulfonic acid, liquid crystal phenomenon is produced at high concentrations to promote the arrangement of carbon nanotubes. However, chlorosulfonic acid is an environmentally unfriendly chemical reagent that is toxic and harmful to the human body. The preparation of carbon nanotube fibers based on chlorosulfonic acid dispersion will still be in the laboratory research stage. Therefore, a safe continuous preparation method for carbon nanotube fibers without chlorosulfonic acid is proposed, which is of great significance to the field of high-performance carbon nanotube fiber preparation technology. Summary of the invention
[0005] Based on the above content, the present invention provides a method for continuously preparing high-conductivity carbon nanotube fibers. The method of the present invention does not require the addition of chlorosulfonic acid and can achieve continuous preparation of high-conductivity carbon nanotube fibers more safely.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] One of the technical solutions of the present invention is a continuous preparation method of high conductivity carbon nanotube fibers, comprising the following steps:
[0008] adding carbon nanotubes and sodium deoxytaurocholate into water and dispersing them to obtain a carbon nanotube dispersion;
[0009] The carbon nanotube dispersion is extruded and injected into a coagulation bath to form gel fibers;
[0010] The gel fiber is twisted and then wound and collected to obtain a high-conductivity carbon nanotube fiber;
[0011] The carbon nanotube is at least one of a single-walled carbon nanotube, a double-walled carbon nanotube or a multi-walled carbon nanotube.
[0012] The second technical solution of the present invention is to prepare high conductivity carbon nanotube fibers according to the above preparation method.
[0013] The third technical solution of the present invention is the application of the above-mentioned high conductivity carbon nanotube fibers in the preparation of human body protection materials and flexible electronic products.
[0014] A fourth technical solution of the present invention is a human body protection material, the raw materials of which include the above-mentioned high-conductivity carbon nanotube fibers.
[0015] A fifth technical solution of the present invention is a flexible electronic product, the raw materials of which include the above-mentioned high-conductivity carbon nanotube fibers.
[0016] The present invention discloses the following technical effects:
[0017] The present invention realizes the continuous preparation of high-performance carbon nanotube fibers without using environmentally unfriendly chemical solvents (chlorosulfonic acid, concentrated sulfuric acid, etc.) that are toxic and harmful to the human body. At the same time, by directly twisting the newly formed gel fibers (i.e., not dried), the orientation and arrangement density of the carbon nanotubes in the fibers are improved, forming carbon nanotube fibers with high density arrangement along the fiber axis, thereby improving the conductivity and strength of the fibers (excellent tensile properties).
[0018] The method of the present invention can realize the continuous production of high-conductivity carbon nanotube fibers, has a simple production process, stable product quality, is easy to prepare on a large scale, and is expected to realize industrial production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 The present invention is a schematic diagram of a device for preparing high-conductivity single-walled carbon nanotube fibers; in the figure, 1 is an extrusion device, 2 is a rotating coagulation bath, 3 is a twisting device, and 4 is a fiber collecting device.
[0021] Figure 2The structure characterization of the untreated original single-walled carbon nanotubes and the dispersed single-walled carbon nanotubes (i.e., the carbon nanotubes in the carbon nanotube dispersion) in Example 1 of the present invention. Wherein, a is a SEM photo of the original single-walled carbon nanotubes, b is an atomic force microscope photo of the dispersed single-walled carbon nanotubes, c is a Raman spectrum of the original single-walled carbon nanotubes, and d is a Raman spectrum of the dispersed single-walled carbon nanotubes.
[0022] Figure 3 The structure and performance characterization of the single-walled carbon nanotube fiber prepared in Example 1 of the present invention; wherein, a is an optical photograph of the single-walled carbon nanotube fiber wound on a winding shaft; b is a low-magnification SEM photograph of the single-walled carbon nanotube fiber; c is a high-magnification SEM photograph of the single-walled carbon nanotube fiber; d is the original data of the tensile curve of the single-walled carbon nanotube fiber.
[0023] Figure 4 The structure and performance characterization of the single-walled carbon nanotube fibers prepared in Comparative Example 1 and Comparative Example 2. Wherein, a is the SEM photo of the single-walled carbon nanotube fibers prepared in Comparative Example 1; b is the SEM photo of the single-walled carbon nanotube fibers prepared in Comparative Example 2; c is the conductivity of the single-walled carbon nanotube fibers prepared in Example 1, Comparative Example 1 and Comparative Example 2; d is the original data of the tensile curves of the single-walled carbon nanotube fibers prepared in Example 1, Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION
[0024] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0025] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0026] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0027] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0028] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0029] A first aspect of the present invention provides a method for continuously preparing high-conductivity carbon nanotube fibers, comprising the following steps:
[0030] adding carbon nanotubes and sodium deoxytaurocholate into water and dispersing them to obtain a carbon nanotube dispersion;
[0031] The carbon nanotube dispersion is extruded and injected into a coagulation bath to form gel fibers;
[0032] The gel fiber is twisted and then wound and collected to obtain a high-conductivity carbon nanotube fiber;
[0033] The carbon nanotube is at least one of a single-walled carbon nanotube, a double-walled carbon nanotube or a multi-walled carbon nanotube.
[0034] The method of the present invention has no strict requirements on the carbon nanotube raw materials needed, and the carbon nanotubes prepared by most manufacturers at present can meet the requirements of the present invention.
[0035] In a preferred embodiment of the present invention, the mass ratio of the carbon nanotubes to the sodium deoxytaurocholate is 1:9.
[0036] The reason why the mass ratio of carbon nanotubes to the sodium deoxytaurocholate is limited to the above parameter ratio is that when the amount of sodium deoxytaurocholate is less than the above ratio, the carbon nanotubes cannot be evenly dispersed in a short time; when the amount of sodium deoxytaurocholate is greater than the above ratio, a large number of bubbles that are difficult to eliminate will appear in the carbon nanotube dispersion, and excess sodium deoxytaurocholate will remain in a large amount in the prepared carbon nanotube fibers.
[0037] Carbon nanotubes themselves are insoluble in water and difficult to be evenly dispersed in water. The present invention achieves even dispersion of carbon nanotubes in water by adding sodium deoxytaurocholate.
[0038] Sodium deoxytaurocholate plays the role of a surfactant in the present invention, and can effectively help (single-walled) carbon nanotubes disperse in water; Sodium deoxytaurocholate has good amphiphilicity, that is, the alkane chain segment is hydrophilic to the surface of (single-walled) carbon nanotubes, and the anion end is hydrophilic, so when (single-walled) carbon nanotubes and sodium deoxytaurocholate are added to water at the same time, the alkane chain end of sodium deoxytaurocholate is firmly adsorbed to the (single-walled) carbon nanotubes through van der Waals force, and the hydrophilic end is used to help the carbon nanotubes disperse in water. Other commonly used surfactants in the art, such as sodium cholate, sodium deoxycholate, sodium dodecyl sulfate, etc., are not suitable for the present invention, and the (single-walled) carbon nanotube dispersion prepared by using the above commonly used surfactants in the art cannot be spun in an acetic acid coagulation bath.
[0039] In a preferred embodiment of the present invention, the concentration of carbon nanotubes in the carbon nanotube dispersion is 0.5-4 mg / mL.
[0040] The reason why the concentration of carbon nanotubes in the carbon nanotube dispersion is limited to the above parameters is that the conductive properties and mechanical properties of the prepared (single-walled) carbon nanotube fibers first increase and then decrease with the increase of the (single-walled) carbon nanotube concentration. When the concentration is low, the fibers are easy to break during the preparation process. When the concentration is too high, the (single-walled) carbon nanotubes are not dispersed evenly. When the concentration is 2 mg / mL, the conductive properties and mechanical properties of the prepared carbon nanotube fibers are the best.
[0041] In a preferred embodiment of the present invention, the dispersion method is ultrasound-assisted dispersion.
[0042] The ultrasound-assisted dispersion is specifically dispersed under probe ultrasound for 15-60 minutes, and then dispersed under water bath ultrasound for 10-30 minutes.
[0043] If the probe ultrasound is omitted and only the water bath ultrasound is used, the (single-walled) carbon nanotubes cannot be untangled from each other and cannot be dispersed in water.
[0044] In a preferred embodiment of the present invention, the extrusion speed is 2-4 mL / h. During the spinning process, gel fibers with different diameters can be obtained by adjusting the spinneret aperture.
[0045] In a preferred embodiment of the present invention, the coagulation bath is acetic acid with a concentration of 40-100 wt %; in a more preferred embodiment of the present invention, the coagulation bath is acetic acid with a concentration of 80-100 wt %.
[0046] The electrical conductivity and mechanical properties of (single-walled) carbon nanotube fibers first increase and then decrease with the decrease in acetic acid concentration. When the acetic acid concentration is 90%, the fiber performance reaches a peak. The reason is that when the acetic acid concentration is higher than 90%, the fiber coagulates too quickly and the solvent exchange is not thorough; when the acetic acid concentration is lower than 90%, the fiber coagulates too slowly, the fiber shrinkage is small, and the internal structure is not compact enough. Therefore, the present invention preferably limits the coagulation bath to acetic acid with a concentration of 40-100wt%, and the most preferred is acetic acid with a concentration of 90wt%.
[0047] The present invention uses sodium deoxytaurocholate as a surfactant, which increases the dispersion concentration of single-walled carbon nanotubes and expands the selection range of the coagulation bath. For example, acetic acid and alcohols can be used as the coagulation bath of the present invention. In a more preferred embodiment of the present invention, the present invention uses acetic acid as a coagulation bath, and the morphology and performance of the prepared fiber are significantly better than those of an alcohol coagulation bath.
[0048] In a preferred embodiment of the present invention, the rotation speed of the twisting process is 800-1200 rpm; the winding and collecting speed of the filament is 8-12 cm / min.
[0049] The twisting treatment can improve the densification of the single-walled carbon nanotube fiber and enhance the arrangement orientation. During the twisting process, the carbon nanotube changes from a random arrangement to an oriented arrangement. The present invention treats the gel fiber by twisting treatment, thereby ensuring the purity of the carbon nanotube fiber, avoiding impurity contamination that is harmful to the fiber performance, and improving the conductivity of the single-walled carbon nanotube fiber.
[0050] The prior art does not disclose twisting treatment before drying (i.e., starting twisting treatment as soon as the fiber is pulled out of the coagulation bath). The present invention uses water as a solvent, and can achieve twisting treatment before drying (the advantage of twisting treatment before drying is that it is easier to achieve the arrangement direction of (single-walled) carbon nanotubes, increase the density of the fiber, and the fiber will further shrink during the drying process to increase the density of the fiber, thereby improving the conductivity and mechanical properties of the fiber.)
[0051] In the prior art spinning methods using other water solvents, it is impossible to prepare gel-like (single-walled) carbon nanotube fibers that are strong enough to support twisting operations, resulting in the inability to twist the carbon nanotube fibers before drying.
[0052] A second aspect of the present invention provides a high-conductivity carbon nanotube fiber prepared according to the above preparation method.
[0053] The method of the present invention can obtain single-walled carbon nanotube fibers with a diameter of 20±1 μm and an electrical conductivity of 0.9×10 6 -1.2×10 6 S / m, tensile strength can reach 750-800Mpa.
[0054] The third aspect of the present invention provides the use of the above-mentioned high-conductivity carbon nanotube fibers in the preparation of human body protection materials and flexible electronic products.
[0055] A fourth aspect of the present invention provides a human body protection material, the raw materials of which include the above-mentioned high-conductivity carbon nanotube fibers.
[0056] A fifth aspect of the present invention provides a flexible electronic product, the raw materials of which include the above-mentioned high-conductivity carbon nanotube fibers.
[0057] The "%" described in the present invention, unless otherwise specified, refers to mass percentage.
[0058] The schematic diagram of the device for preparing high conductivity (single-walled) carbon nanotube fibers of the present invention is as follows Figure 1 As shown; in the figure, 1-extrusion equipment, 2-rotating coagulation bath, 3-twisting equipment, 4-fiber collecting equipment. The extrusion equipment 1 continuously injects the spinning solution into the rotating coagulation bath (acetic acid coagulation bath) 2 through spinnerets of different models. After the spinning solution forms gel fibers in the rotating coagulation bath 2, the fibers are twisted by the twisting equipment 3 to improve the orientation and arrangement density of the (single-walled) carbon nanotubes in the fibers, forming (single-walled) carbon nanotube fibers with high density arrangement along the fiber axis. After the fibers are dehydrated and formed, the fiber collecting equipment 4 is wound and collected. The extrusion speed of the extrusion equipment 1 is adjustable, the rotation speed of the rotating coagulation bath 2 is adjustable, the twisting speed of the twisting equipment 3 is adjustable, and the winding speed of the fiber collecting equipment 4 is adjustable. By adjusting the speed of each component of the device, the continuous production of high conductivity (single-walled) carbon nanotube fibers is achieved.
[0059] Unless otherwise specified, the raw materials used in the embodiments of the present invention can be obtained through commercial sources.
[0060] The single-walled carbon nanotubes used in the embodiments of the present invention have a length of 5-20 μm and a diameter of 1-2 nm.
[0061] The present invention will be further described below by way of examples.
[0062] Example 1
[0063] (1) 40 mg of single-walled carbon nanotubes and 360 mg of sodium deoxytaurocholate were added to 19.6 mL of deionized water, and dispersed for 15 min by probe ultrasound (120 W), and then water bath ultrasound (40 W) was used for 30 min to eliminate bubbles, thereby forming a stable carbon nanotube dispersion (concentration of 0.2 wt%).
[0064] (2) The carbon nanotube dispersion prepared in step (1) is transferred to the extrusion device 1, and a spinneret with a diameter of 0.52 mm is selected, and the extrusion (injection) speed is set to 3.5 mL / h. The carbon nanotube dispersion is injected into an acetic acid coagulation bath (the acetic acid concentration is 90 wt.%, and the vertical insertion depth between the extrusion device and the acetic acid coagulation bath is 3 cm). When the gel fiber is formed, it is pulled out of the acetic acid coagulation bath for twisting treatment (parameter setting: 1000 rpm). Then it is collected by a winding device (winding parameter setting: 10 cm / min) to obtain a continuous single-walled carbon nanotube fiber.
[0065] The untreated original single-walled carbon nanotubes and the dispersed single-walled carbon nanotubes (i.e., the carbon nanotubes in the carbon nanotube dispersion) in step (1) of this embodiment were structurally characterized. The results are as follows: Figure 2 As shown in the figure, a is a SEM photo of the original single-walled carbon nanotube, b is an atomic force microscope photo of the single-walled carbon nanotube after dispersion treatment, c is a Raman spectrum of the original single-walled carbon nanotube, and d is a Raman spectrum of the single-walled carbon nanotube after dispersion treatment. Figure 2 As shown in Figure a, it is a typical SEM photo of the untreated raw single-walled carbon nanotube raw material, in which the single-walled carbon nanotubes are entangled and aggregated. Figure 2 As shown in b, it is a typical atomic force microscope photo of the single-walled carbon nanotube sample after the dispersion treatment obtained in step (1). The single-walled carbon nanotubes are evenly dispersed without obvious entanglement. Figure 2 Figures c and d show the Raman spectra of the original single-walled carbon nanotube sample and the single-walled carbon nanotube sample after dispersion treatment. Comparing the G peak and D peak of the two samples before and after dispersion, it can be seen that the dispersion treatment (addition of sodium deoxytaurocholate + ultrasonic treatment) only causes slight damage to the surface graphitization degree of the carbon nanotubes.
[0066] The single-walled carbon nanotube fibers prepared in step (2) of this example were characterized. Figure 3 shown. Figure 3 (a) is an optical photograph of the prepared single-walled carbon nanotube fiber wound on a winding bobbin. Figure 3 Figures b and c are low-magnification and high-magnification SEM photos of single-walled carbon nanotube fibers, respectively. It can be seen that the single-walled carbon nanotube fibers have a uniform diameter of 19-21 μm, and the single-walled carbon nanotubes inside the fibers are clearly oriented along the fiber axis.
[0067] The performance of the single-walled carbon nanotube fiber prepared in step (2) of this embodiment was characterized. The conductivity of the single-walled carbon nanotube fiber was measured by the four-probe method and was as high as 1.2×10 6 S / m. Figure 3d in the figure is the original data of the tensile curve of the single-walled carbon nanotube fiber prepared in step (2) of this embodiment. The tensile strength of the fiber is 780-800 MPa, and the strain is 4-6%.
[0068] Example 2
[0069] (1) 80 mg of single-walled carbon nanotubes and 720 mg of sodium deoxytaurocholate were added to 19.2 mL of deionized water, and dispersed by probe ultrasound for 30 min, and then water bath ultrasound was used for 30 min to eliminate bubbles, thereby forming a stable carbon nanotube dispersion (concentration of 0.4 wt%).
[0070] (2) Same as step (2) of Example 1. Continuous single-walled carbon nanotube fibers are obtained.
[0071] The diameter of the single-walled carbon nanotube fiber prepared in this example is 24-26 μm, and the conductivity is 0.9×10 6 S / m, tensile strength is 750-770MPa.
[0072] Example 3
[0073] (1) Same as step (1) of Example 1.
[0074] (2) The only difference from step (2) of Example 2 is that the diameter of the spinneret hole is 0.3 mm and the injection speed is 2 mL / h. Continuous single-walled carbon nanotube fibers are obtained.
[0075] The diameter of the single-walled carbon nanotube fiber prepared in this example is 10-11.5 μm, and the conductivity is 1.1×10 6 S / m, tensile strength is 770±20Mpa.
[0076] Comparative Example 1
[0077] The only difference from Example 1 is that the acetic acid coagulation bath in step (2) is replaced by an ethanol coagulation bath.
[0078] Results: When ethanol was used as the coagulation bath, the single-walled carbon nanotube fibers could not be collected completely and continuously, and the twisting process could not be performed.
[0079] The single-walled carbon nanotube fibers prepared in this comparative example were structurally characterized. Figure 4 Figure a is a typical SEM photo of the single-walled carbon nanotube fiber prepared in this comparative example. It is found that the diameter of the single-walled carbon nanotube fiber is about 29-35 μm, and the fiber is uneven.
[0080] The performance of the single-walled carbon nanotube fiber prepared in this comparative example was tested. The conductivity of the single-walled carbon nanotube fiber was measured by the four-probe method to be 0.2×10 6 S / m( Figure 4c). The original data of the tensile curve of the single-walled carbon nanotube fiber prepared in this comparative example is shown in Figure 4 In middle d, the tensile strength of the fiber is 100-125 MPa and the strain is 6-7%.
[0081] Comparative Example 2
[0082] (1) Same as step (1) of Example 1.
[0083] (2) The carbon nanotube dispersion prepared in step (1) is transferred to the extrusion device 1, and a spinneret with a diameter of 0.52 mm is selected, and the extrusion (injection) speed is set to 3.5 mL / h. The carbon nanotube dispersion is injected into an acetic acid coagulation bath (the acetic acid concentration is 90 wt.%, and the vertical insertion depth of the extrusion device and the acetic acid coagulation bath is 3 cm). After the fiber forms a gel, it is pulled out of the acetic acid coagulation bath for drying and then heated at 500° C. in a tubular furnace. Single-walled carbon nanotube fibers are obtained.
[0084] The diameter of the single-walled carbon nanotube fiber prepared in this embodiment is about 32-40 μm.
[0085] The single-walled carbon nanotube fibers prepared in this comparative example were characterized in structure. Figure 4 Figure b is a typical SEM photo of the single-walled carbon nanotube fiber of this comparative example, in which some amorphous carbon particles are generated.
[0086] The single-walled carbon nanotube fiber in this comparative example was tested for performance. The conductivity of the single-walled carbon nanotube fiber was measured by a four-probe method and was as high as 0.6×10 6 S / m( Figure 4 c). The original data of the tensile curve of single-walled carbon nanotube fibers can be found in Figure 4 In middle d, the tensile strength of the fiber is 270–290 MPa at a strain of 1–2%.
[0087] Comparative Example 3
[0088] The only difference from Example 1 is that the twisting step is omitted (ie, the gel fiber is collected by a winding device after being pulled out of the acetic acid coagulation bath).
[0089] The structure and performance of the single-walled carbon nanotube fiber prepared in this comparative example were characterized, and the results were as follows: the single-walled carbon nanotube fiber prepared in this comparative example had a diameter of about 26-29 μm, a tensile strength of 190-210 MPa, a strain of 6-7%, and a conductivity of 0.51×10 6 S / m.
[0090] The results of Examples 1-3 and Comparative Example 1 show that the present invention uses acetic acid as a coagulation bath, which effectively improves the electrical and mechanical properties of the single-walled carbon nanotube fibers, optimizes the structure of the single-walled carbon nanotube fibers, facilitates the continuous production and collection of the fibers, and most importantly, enables the fibers to be twisted after leaving the coagulation bath, further improving the orientation and arrangement density of the single-walled carbon nanotubes in the fibers, and forming highly conductive single-walled carbon nanotube fibers with high density arrangement along the fiber axis, and the electrical conductivity can reach 0.9×10 6 -1.2×10 6 S / m, tensile strength can reach 750-800MPa.
[0091] In addition, the twisting strengthening method of the single-walled carbon nanotube fiber in the present invention avoids the destruction of the carbon nanotube structure by the traditional high-temperature heating treatment method, avoids the generation of impurities in the fiber, ensures the purity of the single-walled carbon nanotube fiber, and at the same time improves the orientation and densification of the carbon nanotubes in the fiber, and promotes the directional transport of electrons and the consistency of force.
[0092] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for continuously preparing high conductivity carbon nanotube fibers, characterized in that: For the following steps: adding carbon nanotubes and sodium deoxytaurocholate into water and dispersing them to obtain a carbon nanotube dispersion; The carbon nanotube dispersion is extruded and injected into a coagulation bath to form gel fibers; The gel fiber is pulled out from the coagulation bath and twisted, and then wound and collected to obtain a high-conductivity carbon nanotube fiber; The carbon nanotube is at least one of a single-walled carbon nanotube, a double-walled carbon nanotube or a multi-walled carbon nanotube; The mass ratio of the carbon nanotubes to the sodium deoxytaurocholate is 1:9; the concentration of the carbon nanotubes in the carbon nanotube dispersion is 0.5-4 mg / mL; The coagulation bath is acetic acid with a concentration of 80-99wt%; The rotation speed of the twisting process is 800-1200 rpm; the winding and collecting speed of the filament is 8-12 cm / min.
2. The method for continuously preparing high conductivity carbon nanotube fibers according to claim 1, characterized in that: The dispersion method is ultrasound-assisted dispersion.
3. The method for continuously preparing high-conductivity carbon nanotube fibers according to claim 1, characterized in that: The extrusion speed is 2-4 mL / h.
4. The high conductivity carbon nanotube fiber prepared according to the preparation method according to any one of claims 1 to 3.
5. Use of the high conductivity carbon nanotube fiber as claimed in claim 4 in the preparation of human body protection materials and flexible electronic products.
6. A human body protection material, characterized in that: The raw material comprises the high conductivity carbon nanotube fiber as claimed in claim 4.
7. A flexible electronic product, characterized in that: The raw material comprises the high conductivity carbon nanotube fiber as claimed in claim 4.
Citation Information
Patent Citations
Method for improving orientation degree and conductivity of carbon nanotube fiber
CN111155217A
Fiber Constituted from Carbon Nanotube and Method for Manufacturing Same
US20210071320A1